Working from Home and Performance Pay: Individual or Collective Payment Schemes? - Uwe Jirjahn; Cinzia Rienzo (Global Labor Organization (GLO), 2024)
Working from home reduces real-time visibility of employees within the physical space of the workplace. This makes it difficult to monitor employees' work behavior. Employers may instead monitor employees' outputs and provide incentives through performance pay. The crucial question is what type of performance pay employers provide to incentivize employees who work from home. Using British panel data, we find that working from home decreases the likelihood of solely receiving individual performance pay. It increases the likelihood of receiving collective performance pay - with or without individual performance pay. This pattern also holds in instrumental variable estimations accounting for endogeneity. Our findings fit theoretical considerations. Working from home means that employees have less opportunities to socialize at work entailing the tendency that they focus on personal achievement and neglect collaboration. Solely rewarding individual performance may reinforce this tendency. By contrast, employers reward collective performance as it counteracts the adverse effects of working from home by providing incentives for collaboration, helping on the job and information sharing.
Keywords: J22; J33; M50; M52; 330; Remote work; face-to-face interaction; helping on the job; information sharing; individual performance pay; profit sharing